Access Regulation and Investment in Next Generation Networks: A Ranking of Regulatory Regimes - Rainer Nitsche; Lars Wiethaus (European School of Management and Technology (ESMT), 2009)
This paper analyses how different types of access regulation to next generation networks affect investments and consumer welfare. The model consists of an investment stage with uncertain returns and subsequent quantity competition. The access price is a function of investment costs and the regulatory regime. A regime with fully distributed costs or a regulatory holiday induces highest investments, followed by risk-sharing and long-run-incremental cost regulation. Risk-sharing creates most consumer welfare, followed by regimes with fully distributed costs, long-run-incremental costs and regulatory holiday, respectively. Risk-sharing benefits consumers as it combines relatively high ex-ante investment incentives with strong ex-post competitive intensity.
urn:nbn:de:101:1-201106143591
Keywords: L51; L96; L10; K23; 650; regulation; competition; telecommunications; broadband; strategic investment; Netzregulierung; Regulierung; Telekommunikation; Investition; Wettbewerb; Konsumentenrente; Spieltheorie; Duopol